Immunohistochemical Expression of P16 Protein and TGF β1 in Mice Liver Exposed to Fumonisin B1 - Mohammed et al. (مجلة بغداد للعلوم)
Fumonisin B1 (FB1) is a mycotoxin produced in some grains (mainly corn) by Fusarium species. Due to a structural similarity between FB1 and sphinganine, sphingolipids metabolism is inhibited. Such inhibition plays a critical role in cell to cell singling and structure of lipoprotein; therefore FB1 has been suggested to have a relationship with human and animal cancer. This research is planned to study the effect of FB1 on male mice at two doses (20 and 30 µg/ ml) on the expression of TGF-β1 and p16 in liver cells. Three groups of Swiss albino male mice; each group was orally administrated with FB1 toxin as the following: normal saline (control group); 20 and 30 µg/ ml. All groups were sacrificed after two weeks of oral management. Liver samples were collected and prepared for immunohistochemistry technique (IHC) using anti-TGF-β1 and anti-p16 antibodies. The results showed that exposure to FB1 caused significant elevation of TGF-β1 in both doses (76.74 ± 2.387% and 80.62 ± 7.277%, respectively) in comparison with the control group (46.79 ± 2.404%). The level of p16 protein was decreased at 20 µg/ml (76.63 ± 2.349%) and then increased at 30 µg/ml (81.25 ± 6.263%) but the expression was lower than that of control (90.00 ± 0.805%). In conclusion, FB1 has a significant effect on TGF-β1 and p16 protein expression at both doses (20 and 30 µg/ml), and therefore, its role in cancer development is suggested.